"I wouldn't want to impose!" Intercultural mediation in French immersion. (1st June 2018) - Keating Marshall, Kelle; Bokhorst‐Heng, Wendy D.
Abstract : This article examines four French immersion (FI) teachers' perspectives on the relationship between language and culture and on their roles as intercultural mediators in New Brunswick (NB), Canada's only officially bilingual province. Data were drawn from semi‐structured interviews with the teachers. Couched in the broader framework of Canada's multicultural policy, the cultural outcomes for NB's FI program underscore the importance of learning French in a multicultural and multilingual society. Understanding the relationship between language and culture is part of this; however, the department explicitly states that it does not intend for immersion students to "adopt" Francophone culture. This analysis shows that these teachers employ a variety of language ideologies, all of which culminate in a "language‐as‐code" approach, devoid of culture and removed from its social contexts of use. They do not consider deep cultural discussions to have a place in their classrooms, although each teacher demonstrates some level of intercultural awareness regarding the language/culture dialectic in their private lives. The works by Kohler (2015 ), Di Stefano (2017 ), and Kearney (2016 ) are employed to consider possible ways forward for teacher training on intercultural mediation in immersion classrooms and on curriculum development to target students' intercultural competence. The Challenge: The cultural learning outcomes for New Brunswick's French immersion program have incongruities. While cultural learning and appreciation are expected, cultural adoption and personal transformation are not. How are these conflicts understood and expressed by classroom teachers, particularly in immersion classrooms?